Pendampingan Penggunaan Aplikasi Akuntansiku Dalam Menyusun Laporan Keuangan Berdasarkan SAK EMKM & KOPERASI Pada Warung Pentol Bakso Toyib Jl. Muhajirin Raya Kota Bengkulu - Astuty, Kamelia; Wati, Ina Sintia; Kurnia, Putri (Universitas Dehasen Bengkulu, 2025)
So far, there are many MSMEs whose financial management is carried out simply. This condition causes MSME owners to be unable to accurately measure the amount of income and costs incurred from these business activities. UMKM Pentol Bakso Toyib only records income / purchases from orders and expenses for production costs and does not make financial reports. This simple recording is done because they do not understand accounting so it is difficult to make financial reports. Financial reports are needed as a means of measuring business performance. The problem that exists in Toyib's Pentol Bakso Business is the limited knowledge of business owners about accounting so they need tools to prepare financial reports. The use of applications can make it easier for MSME actors to prepare their financial reports. Therefore, the community service programme is focused on training in the use of the Akuntansiku application through education on the use of the Akuntansiku application accompanied by explanations of accounting concepts and practices as an effort to improve business owners' accounting knowledge and skills. The owner only needs to input his financial data and the process of preparing his financial statements is carried out systematically in the application. The method of implementing PKM activities is an initial survey to obtain initial data and other financial information, preparation of materials, training and discussion, and evaluation. The results of the activity